Analysis and design of the Dickson charge pump for sub-50 mV energy harvesting. (August 2019) - Machado, Marcio Bender; Nornberg, Franciele; Sawan, Mohamad; Galup-Montoro, Carlos; Schneider, Marcio Cherem
Abstract: This paper presents the analysis and design of a DC/DC boost converter operating from supply voltages around the thermal voltage (26 mV at room temperature), for energy harvesting applications. The boost converter described herein is aimed at starting up DC/DC converters, but its use can be extended to a conventional DC/DC converter in which the power conversion efficiency is not of major concern. Firstly, the operation of the Dickson charge pump for ultra-low voltage is described. Expressions for the output voltage, power conversion efficiency and input resistance are derived. The extremely low voltage operation, made feasible through an enhanced-swing ring oscillator and zero-VT transistors, is demonstrated via a prototype fabricated in 130 nm CMOS technology. For an input voltage of 17 mV, the converter delivers an output current of 10 nA at 1 V output and provides a current of 1 μA at a DC output of 1 V from an input voltage of 23 mV.